Breaking barriers: Sunlight‐activated self‐healing polymers with unprecedented photoaging resistance - Yan Mei Li; Ze Ping Zhang; Min Zhi Rong; Ming Qiu Zhang (SusMat)
Abstract Sunlight‐triggered self‐healing of polymers has attractive advantages, but the same illumination inevitably causes photoaging. The resulting properties deterioration and shortened lifespan run counter to the desire for self‐healing. Herein, the authors propose an innovative solution by introducing carbazolyl‐based dithiocarbamate units. The proof‐of‐concept crosslinked poly(carbazolyl dithiocarbamates‐urethane) shows that the multitasking reactivities of the dynamic bonds stimulated by the sun's ultraviolet rays concurrently implement self‐healing and improve the photoaging resistance. As reflected by the xenon weatherometer measurements, it retains 73.5% of the original strength after 576 h owing to the effects of hydroperoxide intermediates elimination and fluorescence emission. The anti‐photoaging ability is far superior to the control filled with commercial stabilizer. Meantime, networks rearrangement via dynamic exchange reactions among the sunlight‐sensitive dithiocarbamates and long‐range free radicals transfer are allowed in surface layer and the interior, so that the cracks up to 8.5 mm deep are repaired. The work provides a feasible way to break the bottleneck in application of photochemical self‐healing polymers.